MOM AND POP STORE DI KOTA BATAM SETELAH KEHADIRAN INDOMARET DAN ALFAMART : STUDI FENOMENOLOGIS - Tiurniari23 Purba (JURNAL AKUNTANSI BARELANG, 2018)
The mushrooming of modern retailers, especially Indomaret and Alfamart since 2014 in Batam city, is very threatening for the existence of mom and pop stores, especially kiosks located in the area leading to the tourist area. This study highlights what cases caused the number of stalls to decide to close and disperse along the area to the Barelang tourist area and to the Marina tourist area. This type of research uses a qualitative approach with a type of phenomenological study. The sampling technique with the determination of purposive sampling technique with criteria of traders/kiosk owners who have disbanded, namely 10 traders/kiosk owners at the intersection of Barelang and 10 traders / kiosk owners at the intersection of Marina. Results through interviews and observations showed that the presence of Indomaret and Alfamart greatly weakened the opportunity for mom and pop stores. A total of 20 informants, namely mom and pop kiosk owners, especially food and soft drink traders in Batam City, said that this situation made them have to make decisions to close and disband.